PEDAGOGICAL CONDITIONS FOR FORMATION OF READYNESS STUDENTS OF THE FACULTY OF MUSIC AND PEDAGOGICAL USE OF COMPUTER TECHNOLOGIES - L.I. Varnavska (Academy of Cognitive and Natural Sciences, 2008)
The article deals with the developing of pedagogical conditions that form the readiness of students of the musical teacher's training departments to computer technologies practical use in musical compositions ' arrangement.